Penerapan Sistem Ketertelusuran Internal dalam Pengolahan Tuna Sirip Kuning (Thunnus albacares) di PT ABC, Denpasar, Bali - Khairunnisa, Anis; Utami, Ni Made Dwi Rahayu (Food Scientia : Journal of Food Science and Technology, 2024)
Tuna fish is a type of fish that holds high economic value and is in high demand in the sea of Indonesia. The high market demand for tuna products necessitates assurance of safety and quality control, one of which is through the implementation of a traceability system. This research aims to identify the stages of the yellowfin tuna processing process and observe the internal implementation of the traceability system at PT ABC, Denpasar. The research method used is a descriptive-qualitative method with data collection techniques through direct observation and interviews with competent parties such as Quality Control and Quality Assurance teams. The research results show that there are 23 stages in the yellowfin tuna processing process, starting from raw material to delivery. Each stage of the process has a responsible person in-charge to document activities on a paper-based system. Documentation is in the form of daily forms, and coding is done in the form of written codes that indicate specific information. In order to obtain more real-time and integrated information, it is hoped that the company can develop an electronic-based system.